Aplikasi Mobile Berbasis Gamifikasi untuk Edukasi Pemilahan Sampah pada Anak - Rio Brian; Alberino Furqan; Mohammad Rizky Zidan Septiano (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
Waste management remains a significant issue in Indonesia, particularly in the aspect of proper waste sorting. Introducing environmental education to elementary school students is essential to help them develop long-term positive habits. This study presents the design and development of a mobile application aimed at educating elementary school children about correct waste-sorting practices. The application integrates gamification elements—such as points, quizzes, learning modules, and interactive mini-games—to enhance engagement and motivation throughout the learning process. The resulting prototype features a child-friendly interface, educational content on waste categories, and interactive activities designed to reinforce user understanding. This application is intended to function as an engaging and interactive learning tool that makes waste-sorting education more enjoyable, thereby supporting environmental awareness from an early age.